ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI CABAI DI DESA TAMBELANG KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN (Analysis of Factors Affecting Production Chilli Business in Tambelang Village, Maesaan Sub-district, South Minahasa District) - Jeremia Piri; Juliana R. Mandei; Yolanda P. L. Rori (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
This study aims to determine the effect of production factors including NPK â€œMutiaraâ€ fertilizer, pesticides and labor on the production of cayenne pepper farming in Tambelang Village, Maesaan District. This research was carried out for three months from October to December 2021. The sampling method used was the saturated sampling method or census. The sample was all cayenne pepper farmers who had produced. Data used were both primary and secondary data. Primary data was obtained directly from 40 farmers as respondents through interviews with the help of a questionnaire, while secondary data was obtained by searching documents from the Local Agriculture Office. Analysis of the data used wasÂ  regression analysis of the Cobb Douglas model to see the effect of each factor of production on production. The results showed that seeds, pesticides and labor had a significant effect, while the NPK â€œmutiaraâ€Â  fertilizer had no significant effect on the production of cayenne pepper in Tambelang Village, Maesaan District.